2016
DOI: 10.3109/13880209.2016.1158842
|View full text |Cite
|
Sign up to set email alerts
|

Persimmon vinegar and its fractions protect against alcohol-induced hepatic injury in rats through the suppression of CYP2E1 expression

Abstract: Taken together, the present findings suggest that PV and its fractions hold great promise as natural remedies with anti-inflammatory activities that alleviate alcohol-induced liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Persimmon vinegar, obtained from fermented persimmon fruit, is rich in polyphenols, such as gallic acid and catechins, which protect against hydrogen peroxide-induced cellular oxidative stress (Sakanaka and Ishihara, 2008;Zou et al, 2017Zou et al, , 2018. In recent studies, persimmon vinegar, with high potential in the health food market, has been proven to have anti-obesity and anti-inflammatory properties (Ahmed et al, 2016;Lee et al, 2016). Sakanaka and Ishihara, (2008) compared the antioxidant properties of persimmon vinegar and other commercial vinegars (unpolished rice vinegar, polished rice vinegar, and apple vinegar) using radical-scavenging assays.…”
Section: Persimmon Vinegarmentioning
confidence: 99%
“…Persimmon vinegar, obtained from fermented persimmon fruit, is rich in polyphenols, such as gallic acid and catechins, which protect against hydrogen peroxide-induced cellular oxidative stress (Sakanaka and Ishihara, 2008;Zou et al, 2017Zou et al, , 2018. In recent studies, persimmon vinegar, with high potential in the health food market, has been proven to have anti-obesity and anti-inflammatory properties (Ahmed et al, 2016;Lee et al, 2016). Sakanaka and Ishihara, (2008) compared the antioxidant properties of persimmon vinegar and other commercial vinegars (unpolished rice vinegar, polished rice vinegar, and apple vinegar) using radical-scavenging assays.…”
Section: Persimmon Vinegarmentioning
confidence: 99%
“…In addition, some studies showed that fermented persimmon and persimmon vinegar exhibited antioxidant [12] and protective effects against alcohol-induced fat deposition [13] and hepatic injury [14]. Persimmon fruit juice fermented with lactic acid bacteria isolated from kimchi (a Korean traditional fermented vegetable) has been reported [15], and persimmon leaves have been used in the manufacture of fermented functional foods, such as bread and beverages [16][17][18].…”
mentioning
confidence: 99%